Glucocorticoid receptor antagonism reverts docetaxel resistance in human prostate cancer. Issue 1 (19th October 2015) - Kroon, Jan; Puhr, Martin; Buijs, Jeroen T; van der Horst, Geertje; Hemmer, Daniëlle M; Marijt, Koen A; Hwang, Ming S; Masood, Motasim; Grimm, Stefan; Storm, Gert; Metselaar, Josbert M; Meijer, Onno C; et al.
Abstract : Resistance to docetaxel is a major clinical problem in advanced prostate cancer (PCa). Although glucocorticoids (GCs) are frequently used in combination with docetaxel, it is unclear to what extent GCs and their receptor, the glucocorticoid receptor (GR), contribute to the chemotherapy resistance. In this study, we aim to elucidate the role of the GR in docetaxel-resistant PCa in order to improve the current PCa therapies. GR expression was analyzed in a tissue microarray of primary PCa specimens from chemonaive and docetaxel-treated patients, and in cultured PCa cell lines with an acquired docetaxel resistance (PC3-DR, DU145-DR, and 22Rv1-DR). We found a robust overexpression of the GR in primary PCa from docetaxel-treated patients and enhanced GR levels in cultured docetaxel-resistant human PCa cells, indicating a key role of the GR in docetaxel resistance. The capability of the GR antagonists (RU-486 and cyproterone acetate) to revert docetaxel resistance was investigated and revealed significant resensitization of docetaxel-resistant PCa cells for docetaxel treatment in a dose- and time-dependent manner, in which a complete restoration of docetaxel sensitivity was achieved in both androgen receptor (AR)-negative and AR-positive cell lines. Mechanistically, we demonstrated down-regulation of Bcl-xL and Bcl-2 upon GR antagonism, thereby defining potential treatment targets. In conclusion, we describe the involvement of the GR in the acquisition of docetaxel resistance in human PCa. Therapeutic targeting of the GR effectively resensitizes docetaxel-resistant PCa cells. These findings warrant further investigation of the clinical utility of the GR antagonists in the management of patients with advanced and docetaxel-resistant PCa.